1995
DOI: 10.1016/0014-5793(95)00563-o
|View full text |Cite
|
Sign up to set email alerts
|

Alternative system of succinate oxidation in glyoxysomes of higher plants

Abstract: Succinate oxidation in scntella of germinating seeds of wheat and maize was investigated. Besides oxidation via succihate dehydrogenase (SDH; EC 1.3.99.1), an alternative path of succinate oxidation insensitive to SDH inhibitors -malonate and thenoyltrifluoroacetone (TTFA) -was revealed. Using isopicnic sucrose gradient it was shown that this path is localized in glyoxysomal membranes. Glyoxysomal succinate oxidase (GSO) converts succinate directly into malate with the production of hydrogen peroxide identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Fumarase in several plants has not only mitochondrial but also cytosolic localization, and its cytosolic form can be linked to utilization of the glyoxylate cycle products in maize ( Eprintsev et al, 2014 ), in allocation of photosynthates and growth on high nitrogen in Arabidopsis ( Pracharoenwattana et al, 2010 ). Although the main route of succinate metabolism is the mitochondrial complex II, its oxidation can be linked to the reduction of nitrate on plasma membrane ( Wienkoop et al, 1999 ) and to the malonate-insensitive activity of succinate oxidase in glyoxysomes of cereals ( Igamberdiev et al, 1995 ). The coordinated operation of isoenzymes of the TCA cycle enzymes in mitochondria, cytosol and other organelles balances the intercompartmental redox regulation, supplies intermediates for biosynthetic pathways and provides the flexibility of the TCA cycle operation in open versus closed form.…”
Section: Incomplete Tricarboxylic Acid Cycle and The Operation Of Malmentioning
confidence: 99%
“…Fumarase in several plants has not only mitochondrial but also cytosolic localization, and its cytosolic form can be linked to utilization of the glyoxylate cycle products in maize ( Eprintsev et al, 2014 ), in allocation of photosynthates and growth on high nitrogen in Arabidopsis ( Pracharoenwattana et al, 2010 ). Although the main route of succinate metabolism is the mitochondrial complex II, its oxidation can be linked to the reduction of nitrate on plasma membrane ( Wienkoop et al, 1999 ) and to the malonate-insensitive activity of succinate oxidase in glyoxysomes of cereals ( Igamberdiev et al, 1995 ). The coordinated operation of isoenzymes of the TCA cycle enzymes in mitochondria, cytosol and other organelles balances the intercompartmental redox regulation, supplies intermediates for biosynthetic pathways and provides the flexibility of the TCA cycle operation in open versus closed form.…”
Section: Incomplete Tricarboxylic Acid Cycle and The Operation Of Malmentioning
confidence: 99%
“…Catalase activity was determined spectrophotometrically using p-anisidine at 458 nm (Igamberdiev et al 1995). One unit of catalase is defined as the amount that decomposes 1 lmol of H 2 O 2 in 1 min per mg protein in a 15 mM H 2 O 2 solution at pH 7.3 at 26°C.…”
Section: Monitoring Of Enzymatic Activitiesmentioning
confidence: 99%
“…The common agreement is that the metabolism of glyoxysome‐derived succinate involves three enzymes of mitochondria (succinate dehydrogenase, fumarase and malate dehydrogenase) and is connected with gluconeogenesis in the cytosol (see recent review of Graham ); however, in cereals the supply of carbohydrates from starch hydrolysis in the endosperm takes place during the entire process of germination and the role of glyoxylate cycle may be connected more with amino acid synthesis and acidification of the endosperm than with gluconeogenesis (Igamberdiev and Rodionova , Igamberdiev and Popov , reviewed in Igamberdiev and Lea ). Succinate in cereal seeds has also a limited capacity of oxidation in glyoxysomes (Igamberdiev et al ), while amino acid formation takes place in mitochondria, glyoxysomes, plastids and cytosol. The cytosolic form of fumarase, which in Arabidopsis is related to nitrogen metabolism (Pracharoenwattana et al ), may have a direct relation to operation of the glyoxylate cycle because its expression and activity are maximal when the intensity of glyoxylate cycle is peaked.…”
Section: Discussionmentioning
confidence: 99%
“…Based on 14 C‐incorporation to different metabolites, it was shown that the glyoxylate cycle in maize scutellum supplies intermediates for amino acid synthesis and contributes to acidification of endosperm, whereas its role in gluconeogenesis is apparently less significant (Igamberdiev and Rodionova , Igamberdiev and Popov ). Succinate from the glyoxylate cycle can be oxidized in glyoxysomes of cereals (but not dicots) by an oxidase having very low affinity ( K m 18 m M ) and possibly low specificity (Igamberdiev et al ); however, the role of mitochondrial succinate dehydrogenase remains significant (Igamberdiev and Falaleeva , Logan et al ). It was shown earlier that the cytosolic form of fumarase in Arabidopsis is important in nitrogen metabolism, in particular during growth on high nitrogen, by providing malate source for carbon skeletons in amino acid synthesis (Pracharoenwattana et al ).…”
Section: Introductionmentioning
confidence: 99%